1996
DOI: 10.1017/s0950268800058945
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization ofMycobacterium aviumisolates recovered from humans and animals in Australia

Abstract: SUMMARYGenetic relationships amongst 115 mainly Australian isolates of Mycobacterium avium were assessed using multilocus enzyme electrophoresis (MEE). The isolates were divided into 58 electrophoretic types (ETs), with a mean genetic diversity of 0-29. Isolates from humans were closely related to but distinct from those cultured from birds, whilst some porcine isolates belonged to the same ETs as certain human isolates. Pulsed field gel electrophoresis (PFGE) was used to differentiate related isolates, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Second, phenotype-based differentiation may be used in combination with other methods to determine the relationships between species and strains of mycobacteria, especially in samples where DNA is degraded and the results of genetic analysis are unclear. For example, multilocus enzyme electrophoresis (MLEE), based on the variation in enzyme electrophoretic mobility, has been successfully used with a combination of DNAbased methods to distinguish M. paraffinicum from M. scrofulaceum (89) and to differentiate among M. avium (90,91) or M. abscessus (92) isolates. It is important to note that phenotype may significantly influence the data obtained by genotyping methods.…”
Section: Phenotype-based Methodsmentioning
confidence: 99%
“…Second, phenotype-based differentiation may be used in combination with other methods to determine the relationships between species and strains of mycobacteria, especially in samples where DNA is degraded and the results of genetic analysis are unclear. For example, multilocus enzyme electrophoresis (MLEE), based on the variation in enzyme electrophoretic mobility, has been successfully used with a combination of DNAbased methods to distinguish M. paraffinicum from M. scrofulaceum (89) and to differentiate among M. avium (90,91) or M. abscessus (92) isolates. It is important to note that phenotype may significantly influence the data obtained by genotyping methods.…”
Section: Phenotype-based Methodsmentioning
confidence: 99%
“…As well as insights into pathogenicity, MLEE studies have also provided considerable new knowledge on the epidemiology of disease outbreaks associated with a range of bacteria, e.g. Mycobacterium auium (Feizabadi et al, 1996) and Neisseria meningitidis (Weis & Lind, 1996). In this study, we have described a polyphasic approach that attempts to generate an overall view of the population structure of a collection of avian P. multocida isolates.…”
Section: Introductionmentioning
confidence: 99%
“…A significant number of studies have been initiated to understand the epidemiology of these mycobacteria; nevertheless, the origin of MAC infections in humans remains a matter of speculation. It has been suggested that MAC infections in AIDS patients may be caused by a limited number of related M. avium strains Yakrus & Good, 1990), almost invariably belonging to serotypes 1, 4, 6 and 8 (Julander et al, 1996;Yakrus & Good, 1990), but other evidence indicates that they do not represent a single clonal lineage (Feizabadi et al, 1996). Here we address the issue of phylogenetic relationships among M. avium serotypes by using, as markers, genes associated with the strains' serological properties.…”
Section: Resultsmentioning
confidence: 99%